ANALISIS PERMINTAAN PRODUK PETERNAKAN DI DESA TAWAANG KECAMATAN TENGA KABUPATEN MINAHASA SELATAN - Loho, Reynol; Rorimpandey, B; Massie, M T; Santa, N M (Universitas Sam Ratulangi, 2014)
ABSTRACT ANALYSIS OF LIVESTOCK PRODUCT DEMAND AT TAWAANG VILLAGE, TENGA DISTRICT SOUTH MINAHASA REGENCY. The purpose of this study was to determine the number of Â *Alumni Fakultas Peternakan Unsrat **Jurusan Sosial Ekonomi Peternakan Â livestock product demand in Tenga district. The problem this study was how far demand factors such as prices of chicken meat, pork, beef meat, fish, tofu and fermented soybean (tempe) affected the level of demand for livestock products in Tenga district.The total number of samples used in this study were 45 respondents of households. Data collection was conducted during 3 months using the survey method. The analysis used was the model of SUR (Seemingly Unrelated Regression) using the equation of the demand function. The results showed that the numbers of livestock product demand in the Tenga district were chicken meat of 3.04 kg/quarter, pork of 3.24 kg/quarter, beef of 1.29kg/quarter, and egg product of 64.56 eggs/quarter. Therefore; factor of the prices of chicken meat, pork, beef, fish, tofu and fermented soybean (tempe) influenced the demand of livestock products. Keywords: Demand, prices, animal product.